Hubungan Antara Persepsi Pengunjung Kolam Renang Tentang Kondisi Lingkungan dan Fasilitas Sanitasi dengan Minat untuk Kembali Menggunakan - Anindita Riski IsWAri; F.X. Amanto Rahardjo; Haryono Haryono (Poltekkes Kemenkes Yogyakarta, 2014)
One type of public places which has to be supervised in terms of its sanitation is swimming pool because it is related with water usage that may has important role as disease transmission medi-um among the visitors. Good swimming pools must have good environmental conditions and provide appropriate sanitation facilities. The study was aimed to know the relationship between the perception of visitors about those requirements and their interest for coming back. The study locations were three swimmning pools in Sleman Regency as representation of urban, semi ur-ban and rural areas. The study was a survey with cross sectional approach, where by using quo-ta sampling method, a total of 144 visitors were selected as respondents, and were distributed proportionally in each pool. Data about visitors’ perception and interest were obtained by using questionnaire. The results showed that 79,86 % of the respondents have good perception on the environmental conditions of the swimming pools they used; and 81,94 % of the respodents were willing to coming back to the pools some times. A significant but not too strong relationship was found between those perception and interest (p value < 0,001, coeffcient of contingency 0,436); and among the three swimming pools, those perception and interest was found significantly diffe-rent (each p values < 0,001).